Multi Sistem Histiositosis Sel Langerhans pada Anak Laki-Laki Usia 2 Tahun (Tinjauan Histopatologi) - Minna Hasniah; Prasetyadi Mawardi; Ambar Mudigdo; Elok Nurfaiqoh; Fitri Kasmitasari (Jurnal Health Sains, 2021)
Langerhans cell histiocytosis (HSL) or histiocytosis X, eosinophilic granuloma, letterer siwe disease, hand schuller christian disease and hashimoto pritzker disease is a disorder caused by the accumulation and proliferation of langerhans cells in various organs of the body that causes tissue damage. The highest prevalence of HSL occurs in children less than 3 years old, with a ratio of 2:1 for boys and girls. The classic appearance of skin manifestations is an eruption resembling seborrheic dermatitis in the folds, axillae, scalp, retroauricular and trunk areas. The appearance of the lesion is yellow to brownish red papules, purpuric and crusted papules that can occur together with erosion. Histopathological examination with staining with S100 or cluster of differentiation 1a (CD1a) revealed Langerhans cell infiltration. The results of immunohistochemistry with IHC S-100 staining, CD1a showed a picture of Langerhans cells and histiocytes. The purpose of this paper is to study the histopathological features of HSL to better than to diagnosis and treatment of HSL. A 2-year-old boy was consulted with the chief complaint of itchy red nodules on the head, chest and back area. Complaints accompanied by diarrhea, often feel thirsty and hungry and lose weight. Dermatological status in the facial region, the anterior and posterior trunks showed lenticular papules with umbilication (pin points) with erosions covered with necrotic tissue above, on the scalp, facial, retroauricular and trunk regions, yellow to brownish papules were crusted with erosions. Histopathology with hematoxylin and eosin (HE) staining showed the presence of small fragments of skin tissue, the epidermis was partially composed intact, the dermis was filled with histiocytes, plasma cells, eosinophils, mast cell impressions and polymorphonuclear leukocytes. Immunohistochemical examination with staining IHC S-100 and CD1a showed positive. Histiocytosis is a group of disorders characterized by the accumulation of cells derived from dendritic cells accompanied by inflammation and causing tissue damage. Histopathological and immunohistochemical examinations serve to establish the diagnosis. The results of immunohistochemical examination with IHC S-100 staining, CD1a will show a picture of Langerhans cells and histiocytes